2018
DOI: 10.3389/fmicb.2018.00528
|View full text |Cite
|
Sign up to set email alerts
|

Potential Biological and Climatic Factors That Influence the Incidence and Persistence of Highly Pathogenic H5N1 Avian Influenza Virus in Egypt

Abstract: Highly pathogenic H5N1 avian influenza virus (A/H5N1) of clade 2.2.1 is endemic in poultry in Egypt where the highest number of human infections worldwide was reported. During the last 12 years the Egyptian A/H5N1 evolved into several genotypes. In 2007-2014 vaccinated poultry suffered from antigenic drift variants of clade 2.2.1.1 and in 2014/2015 an unprecedented upsurge of A/H5N1 clade 2.2.1.2 occurred in poultry and humans. Factors contributing to the endemicity or re-emergence of A/H5N1 in poultry in Egyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 62 publications
4
21
0
Order By: Relevance
“…HPAI outbreaks have been clustered globally in three Asian countries -Bangladesh, Indonesia and Vietnam and in Middle east in Egypt [ 4 ] with enzootic H5N1-HPAI clinical disease in poultry [ 5 ]. Outside Asia the longest endemic status of H5N1-HPAI is reported in Egypt [ 6 ]. The highest human cases were recorded in Egypt with a case fatality rate coming to 53.2% according to the World Health Organization (WHO) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPAI outbreaks have been clustered globally in three Asian countries -Bangladesh, Indonesia and Vietnam and in Middle east in Egypt [ 4 ] with enzootic H5N1-HPAI clinical disease in poultry [ 5 ]. Outside Asia the longest endemic status of H5N1-HPAI is reported in Egypt [ 6 ]. The highest human cases were recorded in Egypt with a case fatality rate coming to 53.2% according to the World Health Organization (WHO) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Countries like Egypt facing significant changes in their climate likely experience a higher risk of outbreaks [ 15 ].Understanding climate variability factors may enable the expectation and control of future disease events in Egypt [ 6 ]. Unfortunately, the environmental persistence of A/H5N1 is troublesome to evaluate [ 21 ] and prediction based on climate variability has once in a while been assessed, to fill the information crevice, the evidence is required for the effect of them on HPAI-H5N1 outbreaks [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Field observations showed that in contrast to chickens, ducks exhibit mild or no clinical signs after infection with A(H5N1) viruses. Pekin ducks experimentally infected with a clade 2.2.1.2 virus showed no clinical signs or mortality (Salaheldin et al 2018b;Samir et al 2018), suggesting a potential role for ducks in maintaining clade 2.2.1.2 viruses as the dominant virus in Egypt.…”
Section: Biological Properties Of A(h5n1) Viruses In Egyptmentioning
confidence: 99%
“…Despite LPAI H9N2 being endemic in Egypt, the highest H9N2 incidence in domestic birds in the Nile Delta was observed in January 2012, 2013 and 2014 [25,28]. In Egypt, there is evidence for yearround AIV detection in backyard poultry, while AIV infections in backyard and commercial farms seem to peak in winter and spring [15,29].…”
Section: Aiv In Domestic Birds In Egyptmentioning
confidence: 99%
“…Lastly, besides wild bird-related factors, other factors such as those related to climate [29] and, in particular, those related to the poultry industry (including vaccination coverage and efficacy [73] and improper disposal of poultry carcasses [52]) shape the AIV endemicity in Egypt. Hence, evaluation of vaccination coverage and vaccine efficacy under field condition using various analysis as the cumulative annual flock immunity (CAFI) and its correlation with the virus load should be considered.…”
Section: Recommendation: Evidence-based Measures Needed To Improve Prmentioning
confidence: 99%